Internalisasi Standar Etika Publik Bagi Pemimpin Di Lingkungan Birokrasi Pemerintah (Internalization of Public Ethical Standards for Leaders in the Government Bureaucracy) - Kurniadi, Adang (Jurnal Inspirasi, 2020)
Ethics is a topic that grabs the attention of many people or groups in society. This great concern provides an indication of the importance of ethical behavior in society and some important notes on unethical behavior. Ethics is indispensable in government practice so that it can be used as a guide, reference, and guidance on what the government should do. Deviations from regulations, that is a fact that has recently occurred in the world of government. This is the concern of many people so that the ethics of a leader is needed as the community’s expectations can be fulfilled properly. Meanwhile, it is the obligation of a bureaucratic leader to have good ethics in carrying out his duties as a government leader. ABSTRAK Etika merupakan topik yang menyita perhatian banyak orang atau kelompok dalam masyarakat. Perhatian yang besar tersebut memberikan indikasi arti pentingnya perilaku beretika dalam masyarakat dan beberapa catatan penting tentang perilaku tidak beretika. Etika sangat diperlukan dalam praktek pemerintahan untuk dapat dijadikan pedoman, referensi, petunjuk tentang apa yang harus dilakukan oleh pemerintahan. Penyimpangan dari peraturan, itulah fakta yang akhir-akhir ini sering terjadi di dunia pemerintahan. Hal inilah yang menjadi perhatian banyak orang sehingga etika seorang pemimpin sangat diperlukan sebagai harapan masyarakat bisa terpenuhi dengan baik. Sedangkan yang menjadi kewajiban bagi seorang pemimpin birokrasi yaitu memiliki etika yang baik dalam menjalankan tugasnya sebagai pemimpin pemerintahan.